Evidence for Increased Expression of SIRT3 Associated with Hyperandrogenism in Granulosa Cells of Non-Obese PCOS Patients - Shen Zhang; Wenli Deng; Qiongyou Liu; Wei Yang (IMR Press, 2022)
Background: SIRT3 regulates the generation of reactive oxygen species (ROS) in human granulosa cells (GCs). Increased levels of oxidative stress may cause follicular dysplasia in GCs of polycystic ovary syndrome (PCOS) patients. However, expression and regulation of SIRT3 in GCs of PCOS patients have not yet been investigated. The present study is conducted to determine the correlation between SIRT3 and hyperandrogenism in luteinized GCs of PCOS patients. Methods: The mRNA and protein expression of SIRT3 were analysed in the luteinized GCs from the controls and non-obese PCOS patients. Dihydrotestosterone (DHT) was added to the primary cultured GCs to test the effects of androgen excess on intracellular ROS and SIRT3 expression. A DHT-induced PCOS murine model was used to confirm the effects in vivo. Results: In the matched case-control study including 32 pairs of the controls and non-obese PCOS patients, we showed that the expression of SIRT3 was increased in luteinized GCs of non-obese PCOS patients compared with normovulatory controls. Moreover, DHT induced oxidative stress and SIRT3 expression in human GCs, which was further confirmed in a murine PCOS model. Conclusions: These results indicated that the increased expression of SIRT3 was induced by hyperandrogenism in GCs of non-obese PCOS patients.